Causes of cracking of an existing pavement after highway widening in an area of soft soil. Issue 3 (2nd June 2022) - Yu, Heng; Wang, Yimin; Chen, Yekai
Abstract : After the Guangsan expressway in China was widened in 2010–2012, many longitudinal cracks and partial drop-offs appeared in the pavement of both the existing road and the new road. This situation is at odds with the traditional understanding that pavement distress should arise only in the area connecting the new road with the existing one. By considering ( a ) the geological conditions, ( b ) how soft clay consolidates and ( c ) settlement data acquired while the new embankment was being constructed, the following hypothesis is proposed: the additional load applied by the new embankment filling on the existing road foundation caused uneven settlement of the latter, thus causing the existing pavement to crack. A numerical model of the highway widening is established based on the actual project, and the hypothesis is verified by analysing the ground surface settlement and the horizontal displacement in the deep foundation.